Brief perspective of undergraduate students about Transversal Themes: Environment, Health and Sexuality (Research, Society and Development, 2020)
The present work is a qualitative case study that aims to present the perspective of undergraduate students in Natural Sciences and Biology about Transversal Themes (TT): Environment, Health and Sexuality. In all, 25 students were surveyed using a semi-structured questionnaire. The results showed that 58.3% of students are not familiar with TT. When asked about the topics Environment, Health and Sexuality, 68% indicated they had a greater understanding of the Environment. And Health and Sexuality emerged as subjects of greater complexity. By delving into the theme of Environment, the students highlighted the Pampa Biome as a necessary theme to be addressed in basic education and emphasized the diversity of animal life in the state of Rio Grande do Sul and Environmental Education as the main tool in the preservation of this biodiversity. Thus, it was observed that TT may be underdeveloped in academic environments and this may have an impact on teacher training and, consequently, on the training of citizens.